Chapter Dalla storia all'inclusione. Il racconto della comunità cinese di Prato - Finizio, Davide (Public History of Education. Teorie, esperienze, strumenti, 2022)
The contribution describes the connections between attempt in building the history of the chinese community in Prato and the inclusion process activated thanks to the Memory Train in the project of the Tuscany region. As the student Luisa Xu joined the training trip towards the statal Museum in Auschwitz, it has been carried on a project of opening and narration of Chinese people in Italian history. Young generations in the chinese community in Prato have used them as a tool for knowledge and communitarian transformation. From this point of view, processes linked to the Resistance movement have to read in the present as they are addressed to mutual knowledge and to peace.